2018
DOI: 10.3389/fcimb.2017.00536
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Iron, Zinc, and Copper on Dictyostelium discoideum Cell Growth and Resistance to Legionella pneumophila

Abstract: Iron, zinc, and copper play fundamental roles in eucaryotes and procaryotes, and their bioavailability regulates host-pathogen interactions. For intracellular pathogens, the source of metals is the cytoplasm of the host, which in turn manipulates intracellular metal traffic following pathogen recognition. It is established that iron is withheld from the pathogen-containing vacuole, whereas for copper and zinc the evidence is unclear. Most infection studies in mammals have concentrated on effects of metal defic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 114 publications
(192 reference statements)
2
28
0
Order By: Relevance
“…Pathogenic mycobacteria, such as M. marinum or M. tuberculosis , replicate in host cells in a distinct, membrane‐bound pathogen vacuole called MCV, followed by rupture of the vacuole membrane and exit of the bacteria to the cytoplasm (Cardenal‐Munoz et al, ; Koliwer‐Brandl et al, ; Russell, ). The MCV represents a metal ion‐poor environment (Chao et al, ), which is depleted of iron due to the activity of NRAMP‐1, a proton‐driven transporter of ferric iron (Bozzaro, Buracco, & Peracino, ; Buracco et al, ; Buracco, Peracino, Andreini, Bracco, & Bozzaro, ; Peracino, Buracco, & Bozzaro, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pathogenic mycobacteria, such as M. marinum or M. tuberculosis , replicate in host cells in a distinct, membrane‐bound pathogen vacuole called MCV, followed by rupture of the vacuole membrane and exit of the bacteria to the cytoplasm (Cardenal‐Munoz et al, ; Koliwer‐Brandl et al, ; Russell, ). The MCV represents a metal ion‐poor environment (Chao et al, ), which is depleted of iron due to the activity of NRAMP‐1, a proton‐driven transporter of ferric iron (Bozzaro, Buracco, & Peracino, ; Buracco et al, ; Buracco, Peracino, Andreini, Bracco, & Bozzaro, ; Peracino, Buracco, & Bozzaro, ).…”
Section: Discussionmentioning
confidence: 99%
“…Russell, 2016). The MCV represents a metal ion-poor environment (Chao et al, 2019), which is depleted of iron due to the activity of NRAMP-1, a proton-driven transporter of ferric iron Buracco et al, 2015;Buracco, Peracino, Andreini, Bracco, & Bozzaro, 2017;.…”
Section: Marinum δMbtb and δMbtb-δirtab Hyg Are Impaired For Gromentioning
confidence: 99%
“…Here we focused on the Zn 2+ -mediated battle between M. marinum and its host D. discoideum. D. discoideum has previously served as model to uncover the role of transition metals in the resistance to intracellular pathogens Buracco et al, 2017;Buracco et al, 2015;Peracino et al, 2006). For example, it has been shown that whilst Fe 2+ participates in D. discoideum resistance to M. avium or Legionella pneumophila Buracco et al, 2017;Buracco et al, 2015;Peracino et al, 2006), Cu 2+ or Zn 2+ do not affect the infection by the latter (Buracco et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…It has been recently shown that, in D. discoideum, free Zn 2+ accumulates inside (i) the CV network, (ii) zincosomes, endosomal compartments with lysosomal and post-lysosomal characteristics, and (iii) phagosomes containing beads and nonpathogenic bacteria such as Escherichia coli or M. smegmatis Buracco et al, 2017) (Fig. 1A).…”
Section: Free Zn 2+ Accumulates Within Intact M Marinumcontaining Vamentioning
confidence: 99%
“…The drawback to understanding how metazoan hosts have contributed to L. pneumophila evolution is that the evolutionary biology of the immune response has been studied in only two L. pneumophila natural hosts, Dictyostelium discoideum and C. elegans (Buracco, Peracino, Andreini, Bracco, & Bozzaro, 2017;Cardenal-Muñoz, Barisch, Lefrançois, López-Jiménez, & Soldati, 2018;Dunn et al, 2017;Mori, Mode, & Pieters, 2018;Swart, Harrison, Eichinger, Steinert, & Hilbi, 2018;L. Li & Faucher, 2016 Protists resistant to L. pneumophila have also been identified, but their relationship is poorly understood (Amaro, Wang, Gilbert, Roger Anderson, & Shuman, 2015).…”
mentioning
confidence: 99%